Faktor Sosiopsikologis, Emosional Dan Masalah Kesehatan Lansia Di Puskesmas Bojongsari Kabupaten Purbalingga - Rizqiana Wijayanti; Dedy Purwito (Jurnal Keperawatan Muhammadiyah, 2020)
SOCIOPSYCHOLOGICAL AND EMOTIONAL FACTORS AND HEALTH PROBLEMS OF ELDERLY IN BOJONGSARI PUBLIC HEALTH CARE CENTER, PURBALINGGA REGENCY By RIZQIANA WIJAYANTI Universitas Muhammadiyah Purwokerto ABSTRACT Background: The loss of economic independence and physical strength and suffering from various types of degenerative diseases change the elderly from being independent to support individuals to be the people who need help from their children and other family members, as well as from the community in general. The lack of extensive and regular interaction with younger members in the family naturally results in social isolation and the loneliness of the elderly. Lack of beneficial psychological activity turns the person's free time into burdens and boredom which last for the rest of his life. However, the aging process and other psychological or emotional changes occur differently among the elderly because their living conditions depend on various factors such as the nature of the composition, family economic background, and the nature of the relationship. Objective: This research aimed to discover the sociopsychological and emotional factors as well as the health problems of the elderly at Bojongsari Public Health Care Center, Purbalingga Regency. Methods: This was qualitative descriptive research. There were six people taken as the research samples using a snowball sampling technique. Results: The results showed that most respondents had good interactions among the elderly, neighbors, and their families. The emotion of the elderly can be controlled largely and it does not lead to negative directions when they got angry. Four elderly suffered from hypertension. All of them participated in the elderly Integrated Health Service. Conclusion: In Bojong Public Health Care Center most of the elderly have good sociopsychological and emotional condition and the health problem is mostly hypertension. Keywords: Socio-psychological Factors, Emotional and Elderly Health Problems